Investigation of CD47 Expression in Renal Cell Tumors and Evaluation of Its Relationship with Prognostic Parameters - Ömer Faruk Dizibüyük; Zehra Bozdağ; Metin Karakök (Diagnostics)
Background/Objectives: Renal cell carcinoma is an aggressive form of kidney cancer, contributing to an estimated 138,000 deaths globally in 2017. Traditional treatments like chemotherapy and radiation are generally considered ineffective. Additionally, CD47 has been identified as a crucial tumor antigen involved in the development and progression of various cancers, including renal cell carcinoma. The interaction of CD47 with SIRPα triggers a “don’t eat me” signal to the macrophages, inhibiting phagocytosis. Much progress has been made in targeting CD47 for cancer immunotherapy in solid tumors (STs) and hematological malignancies. This study aimed to evaluate CD47 expression in malignant and benign renal cell tumors and compare it with prognostic histopathological parameters. Methods: We included 160 malignant and 26 benign tumors. The malignant tumors consisted of renal cell carcinoma (RCC) subtypes including 37 clear cell, 30 chromophobe, 30 papillary type 1, 29 papillary type 2, and 34 unclassified RCC cases. As for the benign tumors, we included 26 oncocytoma cases. All samples were stained with anti-CD47 antibodies by immunohistochemistry methods. Results: The statistical analysis yielded a significant correlation between CD47 expression and survival, metastasis, and capsule invasion for the unclassified RCC cases. We did not find any further significant correlation between CD47 expression and the studied parameters. Conclusions: To the best of our knowledge, our study is the first to research CD47 expression in benign and malignant renal carcinoma subtypes. Further large-scale studies are needed to determine the expression profile of CD47 in renal cell tumors.